Application of Blood Transfusion Therapy in Postpartum Patients with Anemia in the Mawar Nifas Room at Kardinah Regional General Hospital, Tegal City - Atmaliya, Rully; Sari Purbaningsih, Endah; Fadila, Erida (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Iron deficiency anemia is anemia caused by a lack of iron used for hemoglobin synthesis. General symptoms of anemia include weakness, signs of hyperdynamic state with strong and rapid pulse, and palpitations. Blood transfusion is known to have the potential to overcome anemia, especially anemia in postpartum mothers. Method: This study employed a qualitative approach using a maternal nursing care approach and documented nursing care for anemia patients in the Mawar Postpartum Ward at Kardinah General Hospital in Tegal City. The intervention innovation implemented was the administration of blood transfusion therapy. Result: After continuous blood transfusion for 3 days, the patient showed a decrease in hemoglobin intensity from 7.4 g/dL to 9.0 g/dL. The patient also felt more emotionally calm, with improved dizziness and heart palpitations, and was able to perform activities. Conclusion: Blood transfusion is effective as an additional intervention for managing postpartum anemia patients. This approach also supports maternal nursing practices in improving the quality of care for anemia patients.